The Principal’s Strategy for Improving Accreditation Scores at State Junior High School 4 Dadahup Kuala Kapuas - Enarorika; Anhar Yani; Moh. Heru Budihantho; Septeria Noor Yuliannisa (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2026)
School accreditation serves as a national quality assurance mechanism to evaluate institutional compliance with the Indonesian National Education Standards (SNP). In 2018, SMPN 4 Dadahup Kuala Kapuas received a C accreditation (score 73), with low performance in Graduate Competency Standards, Educator and Education Personnel Standards, and Facilities and Infrastructure Standards. This study aims to analyze the principal’s strategic management in improving accreditation scores, identify institutional constraints, and examine improvement efforts undertaken. The research employs a qualitative post-positivist approach using purposive sampling. Data were collected through observation, interviews, and documentation and analyzed through triangulation involving data reduction, presentation, and conclusion drawing. The findings reveal that the principal adopted administrative compliance–oriented strategies, including formation of an accreditation team, instrument identification, evidence fulfillment, task distribution, and school self-evaluation. Improvement efforts focused on infrastructure procurement, optimization of facilities maintenance, addition of teaching staff, and fulfillment of documentation requirements. However, structural limitations such as limited human resources, inadequate infrastructure, and geographical constraints significantly influenced implementation effectiveness. The study concludes that while strategic compliance strengthened administrative readiness, sustainable accreditation improvement requires structural capacity building beyond document fulfillment.